Thermal performance of outdoor tropical environment - Abu Bakar, Aniza; Abdul Malek, Nurhayati (North Atlantic University Union (NAUN), 2016)
The landscape setting very much shapes the thermal performance of the outdoor environment. The influencing variables are vegetation and ground surface materials among others. This paper presents the impact of landscape settings on the microclimate of three sites with different landscape environment. The investigation was conducted during the wet and dry monsoon seasons of the tropical environment of Malaysia. The study involves field measurement of air temperature, relative humidity and wind environment from 0900hr to 1600hr, conducted on several days of the said monsoon regimes. Significant results in terms of the magnitude of differences of air temperature and relative humidity between the studied sites were observed. The wind environment seems to be also affected by the landscape settings.